Faeco-prevalence of enteric viruses in children under five in Ogun State, Nigeria; a one-year study - Tosin Ogunbiyi; Christianah Idowu Ayolabi; Daniel Kolawole Olukoya; Comfort Obi; Deborah Iyanuoluwa Ayolabi; Adedoyin Esther Onabade; Eunice Ayomide Olawale; Adaobi Emmanuella Unachukwu (Babcock University Medical Journal, 2023)
Objective: Acute gastroenteritis has been reported as the second largest cause of preventable child mortality, accounting for an estimated annual 1.5 million deaths. In Nigeria, routine clinical diagnosis of infectious diarrhoea is bacterial-focused, leaving out the viral agents. Therefore, this study was designed to investigate the prevalence, seasonality, and risk factors of selected enteric viruses (EVs): human adenovirus (HAdV), norovirus (NoV), hepatitis A virus (HAV), and human astrovirus (HAstV) infection in children under 5 years old with acute gastroenteritis in Ogun State, Nigeria.